2011
DOI: 10.1182/blood-2010-08-301283
|View full text |Cite
|
Sign up to set email alerts
|

The small GTPase Rac1 is a novel binding partner of Bcl-2 and stabilizes its antiapoptotic activity

Abstract: The small GTPase Rac1 is involved in the activation of the reduced NAD phosphate oxidase complex resulting in superoxide production. We recently showed that Bcl-2 overexpression inhibited apoptosis in leukemia cells by creating a pro-oxidant intracellular milieu, and that inhibiting intracellular superoxide production sensitized Bcl-2-overexpressing cells to apoptotic stimuli. We report here that silencing and functional inhibition of Rac1 block Bcl-2-mediated increase in intracellular superox-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 46 publications
5
64
1
2
Order By: Relevance
“…These data suggest that the resistance to doxorubicin correlates with the GTP-loaded "active" state of Rac1. This conclusion is supported by a previous study showing that the antiapoptotic protein, Bcl-2, interacts with Rac1 to protect tumor cells from the cytotoxic actions of etoposide and daunorubicin (48). Moreover, our conclusion is also consistent with a previous report suggesting that Rac1 was a potential therapeutic target in chemoradioresistant HNSCC (49).…”
Section: Discussionsupporting
confidence: 82%
“…These data suggest that the resistance to doxorubicin correlates with the GTP-loaded "active" state of Rac1. This conclusion is supported by a previous study showing that the antiapoptotic protein, Bcl-2, interacts with Rac1 to protect tumor cells from the cytotoxic actions of etoposide and daunorubicin (48). Moreover, our conclusion is also consistent with a previous report suggesting that Rac1 was a potential therapeutic target in chemoradioresistant HNSCC (49).…”
Section: Discussionsupporting
confidence: 82%
“…First, Rac1 was shown to interact with Bcl-2 and to stabilize its antiapoptotic activity in lymphoma. 56 Concurrent exposure to NSC-23766 increased the apoptotic effect of the Bcl-2 inhibitor and BH3 mimetic ABT-737 in leukemia cells. 57 Bcl-2 overexpression is a hallmark of CLL 58 .…”
Section: Discussionmentioning
confidence: 97%
“…Recent evidence has shown that Rac1 interacts with Bcl-2 in the mitochondria of lymphocytes, but Bcl-2, rather than Rac1, was coupled to mitochondrial ROS generation (32). In contrast, the ability of Rac1 to translocate into the mitochondria and accept electrons represents a new mechanistic insight into how Rac1 can facilitate the generation of H 2 O 2 by partial reduction of O 2 in macrophages.…”
Section: Discussionmentioning
confidence: 99%